PENERAPAN MODEL PEMBELAJARAN LEARNING START WITH A QUESTION BERBANTUAN GEOGEBRA DALAM PEMBELAJARAN MATEMATIKA - Zakiah _; Dian Nataria Oktaviani; Isnani _ (Jurnal Karya Pendidikan Matematika, 2019)
The purpose of this study is to describe : 1) the ability to understand mathematical concepts taught with GeoGebra assisted LSQ learning models whose values above 60 exceeded 55% and the average exceeded the targeted KKM of 60. 3) the effect of activeness of students taught by GeoGebra assisted LSQ learning model on the ability to understand mathematical concepts. 4) the ability to understand the mathematical concepts of students taught with the GeoGebra assisted LSQ learning model is better than the STAD learning model. The population in this study were class VIII School 1 Talang Tegal District 2018/2019 Academic Year. Sampling using purposive sampling technique. The samples taken were 3 classes namely 1 experimental class, 1 control class and 1 trial class. The method of data collection in this study uses documentation techniques, observation and tests. Data analysis using proportion test and t test one sample, PKPD test, simple linear regression test, and t test one right side. The results of the study stated that : 1) the ability to understand mathematical concepts taught by the GeoGebra assisted LSQ learning model whose scores exceeded the KKM exceeded 55% and the average reached the targeted KKM of 60. 3) there is the influence of GeoGebra's assisted LSQ learning model on the ability to understand mathematical concepts of 66.12%. 4) the ability to understand the mathematical concepts of students taught with the GeoGebra assisted LSQ learning model is better than using the STAD learning model